2020
DOI: 10.1002/dad2.12094
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε 4 and resting‐state functional connectivity in racially/ethnically diverse older adults

Abstract: Introduction Numerous neuroimaging studies demonstrated an association between the apolipoprotein E (APOE) ε 4 allele and resting‐state functional connectivity (rsFC) of regions within the default mode network (DMN), both in healthy populations and patients with AD. It remains unclear whether the APOE ε 4 allele differentially affects the brain's functional network architecture across race/ethnicity. Methods We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…However, no significant difference between the two groups was observed by looking at OCR. While previous studies only analyzed sFNC (Axelrud et al, 2019;Chiesa et al, 2017;McKenna et al, 2016;Turney et al, 2020), the results reported above demonstrated the importance of examining both sFNC and dFNC data to differentiate individuals with different AD risks.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, no significant difference between the two groups was observed by looking at OCR. While previous studies only analyzed sFNC (Axelrud et al, 2019;Chiesa et al, 2017;McKenna et al, 2016;Turney et al, 2020), the results reported above demonstrated the importance of examining both sFNC and dFNC data to differentiate individuals with different AD risks.…”
Section: Discussionmentioning
confidence: 87%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted March 29, 2021. ; https://doi.org/10.1101/2021.03.27.437354 doi: bioRxiv preprint temporal default mode network (DMN) functional connectivity than those without ɛ4 (Turney et al, 2020). Another study showed an increase in functional connectivity between the hippocampus and prefrontal/parietal/temporal cortex in healthy individuals carrying ɛ4 (Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apolipoprotein E ( APOE ) ε4 allele is the most important predictor factor, besides age, of subsequent progression to AD 3 . Remarkable ethnicity‐specific effects of APOE ε4 on AD risk were reported and it is suggested that APOE ε4‐related cognitive impairment is racial‐dependent 4,5 . The apoE protein, mainly produced by liver parenchymal cells, is fundamental to maintain lipoproteins’ structural integrity and to promote their solubilization in blood circulation 6 .…”
Section: Introductionmentioning
confidence: 99%